EDUCATIONAL STRATEGIES OF THE RUSSIAN YOUTH - S. Shapovalova, Inna; V. Kisilenko, Anastasiya; S. Zavodyan, Irina (Gênero & Direito, 2020)
The paper presents the results of our study on the educational strategies of modern Russian youth. As a scientific output, the paper presents the main socialization results of educational attitudes of young people: orientation to education throughout life, the need for self-education, setting up toward obtaining a second higher degree. The main risks that accompany the identified results and the educational paths chosen by young people are identified: the risk of erroneous professional self-identification, the risk of acquiring shallow knowledge and orientation to superficial educational products. As a result of the study, the problematic field of managing the prospects of the educational choice of youth was identified, the perimeter of which comprises the problems related to meeting the needs for self-education of young people, reducing the level and depth of knowledge acquired and stored by youth, the problem of “external memory” associated with an abundance of gadgets and devices that reproduce information, and more.